Observational properties of regular black holes in asymptotic safety - Abdybek Urmanov; Hrishikesh Chakrabarty; Daniele Malafarina (European Physical Journal C: Particles and Fields)
Abstract We consider the observational properties of a spherically symmetric, static regular black hole within the framework of asymptotic safety (AS) as proposed by Bonanno et al. The metric resembles the Schwarzschild solution in the classical limit. The departure from Schwarzschild at small scales is controlled by a single free parameter related to the ultraviolet (UV) cutoff of the theory. We investigated null and time-like geodesics around the AS metric, including circular orbits, photon rings and lensing effects. In particular we focused on the optical properties of thin accretion disks in the equatorial plane of the object and compared them with those of accretion disks in the Schwarzschild metric. We found that the radiation flux, luminosity, and efficiency of the accretion disk increase with the value of the free parameter. Using a spacetime generic open-source relativistic ray-tracing code, we simulate the K $$α $$ α iron line profiles emitted by the disk and analyze their deviation from that of the Schwarzschild geometry.